Commentary on the MID3 Good Practices Paper. (22nd July 2017) - Manolis, Efthymios; Brogren, Jacob; Cole, Susan; Hay, Justin L.; Nordmark, Anna; Karlsson, Kristin E.; Lentz, Frederike; Benda, Norbert; Wangorsch, Gaby; Pons, Gerard; Zhao, Wei; Gigante, Valeria; et al.
Abstract : During the last 10 years the European Medicines Agency (EMA) organized a number of workshops on modeling and simulation, working towards greater integration of modeling and simulation (M&S) in the development and regulatory assessment of medicines. In the 2011 EMA – European Federation of Pharmaceutical Industries and Associations (EFPIA) Workshop on Modelling and Simulation, European regulators agreed to the necessity to build expertise to be able to review M&S data provided by companies in their dossier. This led to the establishment of the EMA Modelling and Simulation Working Group (MSWG). Also, there was agreement reached on the need for harmonization on good M&S practices and for continuing dialog across all parties. The MSWG acknowledges the initiative of the EFPIA Model‐Informed Drug Discovery and Development (MID3) group in promoting greater consistency in practice, application, and documentation of M&S and considers the paper is an important contribution towards achieving this objective.